2008
DOI: 10.1115/1.2909184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pin Tip Clearance on Flow and Heat Transfer at Low Reynolds Numbers

Abstract: Cylindrical pin fins with tip clearances are investigated in the low Reynolds number range 5<ReD<400 in a plane minichannel. Five tip gaps are investigated ranging from a full pin fin (t*=0.0) to a clearance of t*=0.4D*, where D* is the pin diameter. It is established that unlike high Reynolds number flows, the flow and heat transfer are quite sensitive to tip clearance. A number of unique flow effects, which increase the heat transfer performance, are identified. The tip gap affects the heat transfer co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…They reported a Nusselt number augmentation factor of 3 and conductance augmentation factor of 5. They found that a clearance at one end of the fin reduced the end wall effects which negatively impact heat transfer [33]. Rozati et al also found that at Reo < 400, that clearances of f = 0.1 H and 0.4 H provided the greatest augmentation of the convective heat transfer coefficient and conductance by factors of 3.2 and 4.6, respectively.…”
Section: D<02mentioning
confidence: 94%
See 4 more Smart Citations
“…They reported a Nusselt number augmentation factor of 3 and conductance augmentation factor of 5. They found that a clearance at one end of the fin reduced the end wall effects which negatively impact heat transfer [33]. Rozati et al also found that at Reo < 400, that clearances of f = 0.1 H and 0.4 H provided the greatest augmentation of the convective heat transfer coefficient and conductance by factors of 3.2 and 4.6, respectively.…”
Section: D<02mentioning
confidence: 94%
“…This paper reports work that follows on the work by Rozati et al [33] by examining pin fins with a clearance at both ends and extending the Reynolds number range to 10 < Reo < 600. A constant heat flux is specified on the fins and plate walls.…”
Section: D<02mentioning
confidence: 96%
See 3 more Smart Citations